Do Dictionaries Help ESL/EFL Students Improve Their Reading Comprehension Skills? - D’Souza, Gregory (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1994)
An analysis of some of the ways in which learners’ dictionaries are used in ESL/EFL classes reveals that very little is done by teachers in the way of teaching students dictionary-using strategies to improve their reading comprehension skills. Traditional ways of approaching dictionary use with reference to monolingual and bilingual dictionaries are discussed. Practical suggestions for the use of dictionaries in improving L2 reading skills are then made.1